2008
DOI: 10.1037/a0013811
|View full text |Cite
|
Sign up to set email alerts
|

Biofeedback-based behavioral treatment for chronic tinnitus: Results of a randomized controlled trial.

Abstract: Many tinnitus sufferers believe that their tinnitus has an organic basis and thus seek medical rather than psychological treatments. Tinnitus has been found to be associated with negative appraisal, dysfunctional attention shift, and heightened psychophysiological arousal, so cognitive-behavioral interventions and biofeedback are commonly suggested as treatments. This study developed and investigated the efficacy of a biofeedback-based cognitive-behavioral treatment for tinnitus. In total, 130 tinnitus patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 69 publications
0
55
0
6
Order By: Relevance
“…In our sample, a lower rate of female participants (39.4%) was found. Other tinnitus studies show an approximately equal distribution of gender (e.g., 46.9% females in the meta-analysis by Hesser et al), however, some trials conducted in Germany also report lower rates of female participants, i.e., 33 -38% (Kröner-Herwig, Hebing et al, 1995;Weise, Heinecke et al, 2008;Zachriat & Kröner-Herwig, 2004). In addition, a high level of education was found.…”
Section: M=4024 Sd=1223)mentioning
confidence: 87%
See 1 more Smart Citation
“…In our sample, a lower rate of female participants (39.4%) was found. Other tinnitus studies show an approximately equal distribution of gender (e.g., 46.9% females in the meta-analysis by Hesser et al), however, some trials conducted in Germany also report lower rates of female participants, i.e., 33 -38% (Kröner-Herwig, Hebing et al, 1995;Weise, Heinecke et al, 2008;Zachriat & Kröner-Herwig, 2004). In addition, a high level of education was found.…”
Section: M=4024 Sd=1223)mentioning
confidence: 87%
“…In particular, cognitive-behavioural treatment (CBT) approaches have been shown to be effective in reducing tinnitus distress (Hesser, Weise, Westin, & Andersson, 2011). These interventions include strategies to change both dysfunctional behaviours and cognitions associated with tinnitus (e.g., Weise, Heinecke, & Rief, 2008;Zachriat & Kröner-Herwig, 2004). Commonly used strategies are for instance attention shift from the tinnitus to enable habituation, exposure to noises and/or to silence to reduce avoidance behaviour, or identification and modification of dysfunctional beliefs to enhance tinnitus acceptance.…”
Section: Introductionmentioning
confidence: 99%
“…40 Relax ation therapy does benefi t patients. 42 Formal CBT was shown to reduce tinnitus distress in systematic review and meta-analysis, 43,44 although these studies involved patients suffi ciently distressed as to warrant referral to a psychologist, and therapy was undertaken by expert practitioners, which could limit applicability to a general clinic. 45 A prescriptive treatment protocol for tinnitus called tinnitus retraining therapy (TRT) 46 includes counselling and sound-generator therapy.…”
Section: Standard Treatmentsmentioning
confidence: 99%
“…Cognitive behavioral therapy (CBT) is one of the most-researched tinnitus management interventions but is rarely offered in clinical practice [3,4]. The effect of CBT on tinnitus distress has been demonstrated in reviews and meta-analyses [5,6,7]. Furthermore, a recent study by Cima et al [8] revealed that a specialized CBT treatment for tinnitus had a high potential for widespread implementation in routine health care.…”
mentioning
confidence: 99%